COMPOSITION AND DENSITY OF MACRO MARINE DEBRIS IN THE MANGROVE AREA OF KERAMAT VILLAGE MANANGGU SUB-DISTRICT BOALEMO REGENCY - Mohamad Aldi Alex Ikano; Faizal Kasim; Kadim, Miftahul Khair; Muthmainnah, Muthmainnah (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2023)
This study aims to determine the composition and density of macro marine debris in the mangrove area of Keramat Village, Mananggu Sub-District, Boalemo Regency. This research was carried out from August to September 2021. Data collection was carried out using a purposive sampling survey method using 3 line transects to collect macro-sized waste types. The results of the study found that several types of waste in the mangrove area of Keramat Village consisted of plastic and non-plastic waste. The composition of plastic waste amounted to 99.14%, and non-plastic waste was 0.86%. The highest density was found in line transect 1 with a value of 6500 amount/ha.